1988
DOI: 10.1128/jvi.62.7.2285-2290.1988
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus RNA replication in vitro: synthesis of viral template RNAs and virion RNAs in the absence of an added primer

Abstract: The two steps in influenza virus RNA replication are (i) the synthesis of template RNAs, i.e., full-length copies of the virion RNAs, and (ii) the copying of these template RNAs into new virion RNAs. We prepared nuclear extracts from infected HeLa cells that catalyzed both template RNA and virion RNA synthesis in vitro in the absence of an added primer. Antibody depletion experiments implicated nucleocapsid protein molecules not associated with nucleocapsids in template RNA synthesis for antitermination at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 28 publications
1
97
0
Order By: Relevance
“…Furthermore, NP can interact with several cellular proteins, including filamentous (F) actin (Digard et al, 1999), nuclear import receptors of the importin-a class (O'Neill and Palese, 1995), the nuclear export receptor CRM1 (Elton et al, 2001) The RNP complex is the basic functional unit for replication and transcription of influenza viral genome. Previous data have shown that the template-size RNA can not be synthesized if there is no NP in the RNP complex (Honda et al, 1988), and NP is essential for the synthesis of vRNA and cRNA (Shapiro and Krug, 1988). Several hypotheses have been proposed for the role of NP in the switch between mRNA and cRNA synthesis (Portela and Digard, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NP can interact with several cellular proteins, including filamentous (F) actin (Digard et al, 1999), nuclear import receptors of the importin-a class (O'Neill and Palese, 1995), the nuclear export receptor CRM1 (Elton et al, 2001) The RNP complex is the basic functional unit for replication and transcription of influenza viral genome. Previous data have shown that the template-size RNA can not be synthesized if there is no NP in the RNP complex (Honda et al, 1988), and NP is essential for the synthesis of vRNA and cRNA (Shapiro and Krug, 1988). Several hypotheses have been proposed for the role of NP in the switch between mRNA and cRNA synthesis (Portela and Digard, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms of this broad inhibition of some siRNAs are still not very clear yet. From the standpoint of viral target choice in RNAi based antiviral therapy, NP protein is required for elongation and antitermination of nascent cRNA and vRNA transcripts [33,34]. Without newly synthesized NP, further viral transcription and replication are blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that NP is important for virus genome replication (Shapiro and Krug, 1988;Medcalf et al, 1999). NP is required for elongation of RNA synthesis (Honda et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…NP is required for elongation of RNA synthesis (Honda et al, 1988). Moreover, the in vitro cRNA synthesis using infected cell extracts as an enzyme source depends on a supply of non-RNP-associated NP (Shapiro and Krug, 1988). The latter finding may be interpreted as that NP functions in co-transcriptional encapsidation of nascent RNA for prevention of discrete RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation